Strategi Komunikasi Dakwah Akun Instagram @yufid.tv: Analisis Semiotika Charles Sanders Peirce - Faridah, Alfi Nurul; Anam, Moh Khoirul (Journal of Islamic Communication Studies, 2024)
This research explores the da’wah communication strategies employed by the @yufid.tv Instagram account, with a specific focus on the application of da’wah communication techniques in conveying da’wah messages through Motion Graphic video content. The primary aim is to discern the da’wah communication techniques utilized by the @yufid.tv Instagram account. Employing a qualitative approach with a descriptive method, the study selectively samples data purposively from the account and subsequently applies Charles Sanders Peirce's triadic semiotics for analysis. The research findings reveal that @yufid.tv employs sentimental da’wah techniques, integrating narrative sentences into the video's dialogue text to evoke emotional resonance and gentleness. Rational techniques are also employed, rooted in the Quran, hadiths, and excerpts from the stories of the Prophet or the Prophet's Companions, complemented by relevant animated illustrative images. Meanwhile, sensory techniques leverage human sensory perception through visually appealing audio-visual elements and graphic designs. Additionally, the incorporation of hashtags facilitates the visibility of Motion Graphic videos on other users' feeds. This research provides valuable insights into diverse and effective da’wah communication strategies implemented by @yufid.tv on Instagram.